Disrupted structural and functional connectivity networks in ischemic stroke patients. (19th November 2017) - Zhang, Jingna; Zhang, Ye; Wang, Li; Sang, Linqiong; Yang, Jun; Yan, Rubing; Li, Pengyue; Wang, Jian; Qiu, Mingguo
Highlights: Patients with stroke exhibit abnormal global and nodal characteristics in structural and functional brain networks. The decreased nodal degree of the IPL correlated positively with reduced motor ability (FMA) in patients with stroke. The decreased nodal betweenness of the PCG correlated positively with poor immediate recall ability in patients with stroke. Patients with stroke showed decreased network coupling between the structural and functional networks. A significant positive correlation between network coupling strength and the FMA score was observed in patients with stroke. Abstract: Local lesions caused by stroke may result in extensive structural and functional reorganization in the brain. Previous studies of this phenomenon have focused on specific brain networks. Here, we aimed to discover abnormalities in whole-brain networks and to explore the decoupling between structural and functional connectivity in patients with stroke. Fifteen ischemic stroke patients and 23 normal controls (NCs) were recruited in this study. A graph theoretical analysis was employed to investigate the abnormal topological properties of structural and functional brain networks in patients with stroke. Both patients with stroke and NCs exhibited small-world organization in brain networks. However, compared to NCs, patients with stroke exhibited abnormal global properties characterized by a higher characteristic path length and lower global efficiency. Furthermore, patients with stroke showed altered nodal characteristics, primarily in certain motor- and cognition-related regions. Positive correlations between the nodal degree of the inferior parietal lobule and the Fugl-Meyer Assessment (FMA) score and between the nodal betweenness centrality of the posterior cingulate gyrus (PCG) and immediate recall were observed in patients with stroke. Most importantly, the strength of the structural–functional connectivity network coupling was decreased, and the coupling degree was related to the FMA score of patients, suggesting that decoupling may provide a novel biomarker for the assessment of motor impairment in patients with stroke. Thus, the topological organization of brain networks is altered in patients with stroke, and our results provide insights into the structural and functional organization of the brain after stroke from the viewpoint of network topology.